1994
DOI: 10.1111/j.1365-2869.1994.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep spindle frequency changes during the menstrual cycle

Abstract: Five healthy adult women aged 20 to 28 had 12-15 polysomnographic recordings, as well as daily basal body temperature and multiple LH, FSH, estrogen and progesterone measurements taken during a single menstrual cycle. Sleep stages were scored both visually and with a spindle and delta-wave, real-time, automatic analysing system. A cubic growth-curve model showed that the frequency of sleep spindles changed markedly over the menstrual cycle: spindle frequency was lowest about 18 days before onset of menses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 12 publications
1
32
1
Order By: Relevance
“…non-perimenses). Regarding Stage 2 sleep features (i.e., spindles, slow oscillations and spindle/SO events), unlike prior reports (Ishizuka et al, 1994;Genzel et al, 2012), we did not find differences in spindle events based on sex and hormone phase, which may be due in part to the use of different menstrual cycle categories in this study. Additionally, we did not observe differences in SO events or spindle/SO coincidences between men and women, and no differences due to menstrual phase.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…non-perimenses). Regarding Stage 2 sleep features (i.e., spindles, slow oscillations and spindle/SO events), unlike prior reports (Ishizuka et al, 1994;Genzel et al, 2012), we did not find differences in spindle events based on sex and hormone phase, which may be due in part to the use of different menstrual cycle categories in this study. Additionally, we did not observe differences in SO events or spindle/SO coincidences between men and women, and no differences due to menstrual phase.…”
Section: Discussioncontrasting
confidence: 56%
“…It is unclear whether these sex differences in spindle activity relate to meaningful functional differences or whether they are simply an artifact from differences in skull thickness that amplifies the detection of spindles in women (cite check Dijk et al, 1988). In addition, it has been shown that spindle activity increases during luteal phase compare to follicular phase (Baker at., 2007;Baker et al, 2012, Driver et al, 1996Ishizuka et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Ho [21] reported an increase in SWS in the luteal phase, but most previous studies, including earlier studies done in our laboratory, have found no change in SWS [3,4,14,28] or slow wave activity [14,22] in the luteal phase compared to the follicular phase. Instead, these studies have found decreased REM sleep [3], decreased latency to SWS [4], decreased ROL [28], or increased stage-2 sleep [14] in the luteal phase compared to the follicular phase.…”
Section: Discussionmentioning
confidence: 92%
“…Although there have been numerous studies investigating sleep during the natural menstrual cycle, the findings once again are inconsistent (see [13] for review). In the luteal phase, rapid eye movement (REM) sleep has been reported to be either reduced [3,14] or unchanged [4], and stage-2 non-REM sleep has been reported to increase in association with increased activity in the spindle frequency range (12)(13)(14)(15) [14,22], or remain unchanged [3,28]. Changes that occur in sleep during the menstrual cycle are thought to be associated with changes in progesterone [14], but the variability and the confounding interactions that occur between hormonal systems in the menstrual cycle make it difficult to attribute any variation in sleep to one hormone.…”
Section: Introductionmentioning
confidence: 99%
“…Because the experimental schedule is determined by each subject's clinical and personal needs, the time of day when subjects trained on the task was not controlled, nor was the time between task performance and sleep onset. Spindle rate is known to be affected by multiple factors including age, sex, menstrual cycle, and intelligence (32)(33)(34). For this reason absolute differences in spindle rate should not be compared between subjects; instead a relative difference is used to measure within-subject changes.…”
Section: Resultsmentioning
confidence: 99%